VIABILITAS BAKTERI PROBIOTIK IN-VITRO DAN PENGARUH PEMBERIAN AIR OKSIGEN TERHADAP PERTUMBUHAN BAKTERI PROBIOTIK SECARA IN-VIVO - Enok sobariah; Ali Khomsan; Ingrid S. Surono (Food and Nutrition Society of Indonesia, 2007)
The aim of this study were to identify the in-vitro tolerance of pro-biotic bacteria to acid and bile salt condition; and to prove a hypothesis that the supplementation of oxygenated water has a positive effect on the body weight of rat and on viability of pro-biotic bacteria. The first study was carried out at PAU Laboratory of Bogor Agricultural University, while the second study was conducted at Department of Community Nutrition of Bogor Agricultural University and Microbiology Laboratory of Indonesia Institute of Technology. Forty five rats aged 6 weeks were divided into three groups, i.e., control group without probiotic (a0), Lactobacillus casei Shirota (a1), and Lactobacillus IS-7257 (a2). Each group (consisting of 5 rats each) has three different treatments, namely, control without oxygenated water (b0), 50 ppm oxygenated water (b2), and 80 ppm oxygenated water (b2). Oxygenated water was administered to the rats twice a day in the morning (3.25 ml) and afternoon (3.00 ml). Observation was carried out on the body weight of the rats, fecal lactic acid bacteria, coliform, and anaerob bacteria by plate counting, for 4 periods, i.e, prior to the treatment (C0), after three-day treatment (C1), after seven-day treatment (C2), and on the 10th day treatment or three days after washed out period. The results indicated that probiotic bacteria are resistant to acid and bile acid condition. Oxygen concentration in water has a significant positive influence on the body weight of rats towards viability of probiotic bacteria (p-level < 0.05). The supplementation of oxygenated water 50 ppm significantly increase the population of viable fecal lactic acid bacteria in L. casei Shirota and Lactobacillus IS-7257 groups after 3 and 7 days of treatment. Lactobacillus IS-7257 gave better response than L. casei Shirota. The supplementation of oxygenated water 80 ppm significantly reduces the fecal coliform in-vivo in both L. casei Shirota and Lactobacillus IS-7257 groups (p-level < 0.05).